P8. Social brain network and autism spectrum disorder: Reduced connectivity to the frontal cortex. Issue 8 (August 2015) - Hoffmann, E.; Brück, C.; Kreifelts, B.; Ethofer, T.; Wildgruber, D.
<x xml:space="preserve">Abstract</x> Subjects with autism spectrum disorder (ASD) consistently present with difficulties in social interaction. We presumed that in subjects with ASD social impairments might be associated with decreased activation and coupling of specific brain regions. We examined ASD-related differences in the activation and connectivity of brain areas involved in the processing of facial, vocal and audiovisual social signals (i.e. fusiform face area (FFA), temporal voice area (TVA), and amygdala; Refs. (Brück et al., 2011; Wicker et al., 2008)). 10 adult subjects with ASD and 20 typically developed (TD) control subjects took part in the study. Data was obtained using a 3T scanner (Siemens TRIO, BOLD-fMRI, 2D-EPI sequence: TR = 1700 ms, TE = 30 ms, 30 slices, 4 mm thickness + 1 mm gap). Three functional blocked-design localizers were used to define brain areas involved in the processing of facial, vocal, and audiovisual social signals (Refs. Kreifelts et al., 2010; Kreifelts et al., 2009). Data was analyzed using SPM8. Differences between TD controls and ASD subjects were explored by comparing activation pattern between groups (ASD vs. TD). Different psychophysiological interaction (PPI) analyses aimed at identifying brain regions showing altered connectivity with the FFA, the TVA, and the amygdala were used to infer group differences in the connectivity. Statistical thresholds were set at a height threshold of p ⩽ 0.01 and a cluster-wise significance level of p < 0.05 corrected for multiple comparisons. PPI Faces (Fig. 1). (a) Group comparison: ASD subjects vs. TD controls. PPI analysis showed a decreased connectivity between the right amygdala and the left inferior frontal cortex in the group of ASD subjects (x = −39, y = 41, z = 8). (b) Correlation analysis with AQ scores: Connectivity was negatively correlated with AQ scores between the right amygdala and the left inferior frontal and the left frontoorbital cortex, respectively (x = −38, y = 41, z = 3). PPI Voices (Fig. 2). (a) Group comparison: ASD subjects vs. TD controls. Highlighted areas in the medial frontal cortex indicate regions with decreased connectivity to the right TVA in ASD subjects (x = 2, y = −16, z = 16). (b) Correlation analysis with AQ scores: Connectivity between the left TVA and the right frontal superior cortex was inversely correlated with AQ scores (x = 20, y = 16, z = 23). In ASD patients we found reduced connectivity of the amygdala and TVA with frontal brain areas known to be involved in social cognitive processes such as evaluating social information. Future research should aim to clarify whether the decreased cerebral connectivity should rather be considered the cause or the consequence of impaired social interactions in ASD.